Limitation Of The Crime Of Embezzlement Of Foundation Financial Management - Dodi Togatorop; Evi Retno Wulan (JURNAL HUKUM SEHASEN, 2024)
The alleged misappropriation of funds by the Aksi Cepat Tanggap (ACT) Foundation has attracted public attention in Indonesia and raised questions about the use of Foundation funds, especially funds derived from public donations. This research aims to analyze whether the use of Foundation funds for salaries and the use of funds that are not in accordance with the program can meet the elements of the crime of embezzlement. The method used in this research is normative legal research using secondary data, such as laws and regulations, literature, and previous research results. The results of the analysis show that the use of Foundation funds for salaries can fulfill the elements of embezzlement crime if it meets three certain criteria, namely the receipt of salaries by the Foundation management, the relationship between the management and the founder of the Foundation, and the non-implementation of the Foundation's management directly and fully. Not only that, the use of Foundation funds that are not in accordance with the program can also fulfill the elements of embezzlement if it meets three criteria, namely the use of funds for personal interests, interests that are not in line with the objectives of the Foundation, and interests that are contrary to the Articles of Association of the Foundation.